Novel Designed Proteolytically Resistant VEGF-B186R127S Promotes Angiogenesis in Mouse Heart by Recruiting Endothelial Progenitor Cells - Mallick, Rahul; Gurzeler, Erika; Toivanen, Pyry I.; Nieminen, Tiina; Ylä-Herttuala, Seppo (Frontiers in Bioengineering and Biotechnology, 2022)
Background: Previous studies have indicated that vascular endothelial growth factor B186 (VEGF-B186) supports coronary vascular growth in normal and ischaemic myocardium. However, previous studies also indicate that induction of ventricular arrhythmias is a severe side effect preventing the use of VEGF-B186 in cardiac gene therapy, possibly mediated by binding to neuropilin 1 (NRP1). We have designed a novel VEGF-B186 variant, VEGF-B186R127S, which is resistant to proteolytic processing and unable to bind to NRP1. Here, we studied its effects on mouse heart to explore the mechanism of VEGF-B186-induced vascular growth along with its effects on cardiac performance. Methods: Following characterization of VEGF-B186R127S, we performed ultrasound guided adenoviral VEGF-B186R127S gene transfers into murine heart. Vascular growth and heart functions were analysed using immunohistochemistry, RT-PCR, electrocardiogram and ultrasound examinations. Endothelial progenitor cells (EPCs) were isolated from the circulating blood and characterized. Also, in vitro experiments were carried out in cardiac endothelial cells with adenoviral vectors. Results: The proteolytically resistant VEGF-B186R127S significantly induced vascular growth in mouse heart. Interestingly, VEGF-B186R127S gene transfer increased the number of circulating EPCs that secreted VEGF-A. Other proangiogenic factors were also present in plasma and heart tissue after the VEGF-B186R127S gene transfer. Importantly, VEGF-B186R127S gene transfer did not cause any side effects, such as arrhythmias. Conclusions: VEGF-B186R127S induces vascular growth in mouse heart by recruiting EPCs. VEGF-B186R127S is a novel therapeutic agent for cardiac therapeutic angiogenesis to rescue myocardial tissue after an ischemic insult.